Optimizing health system response to patient's needs: an argument for the importance of functioning information. Issue 19 (11th September 2018) - Hopfe, Maren; Prodinger, Birgit; Bickenbach, Jerome E.; Stucki, Gerold
Abstract: Background: Current health systems are increasingly challenged to meet the needs of a growing number of patients living with chronic and often multiple health conditions. The primary outcome of care, it is argued, is not merely curing disease but also optimizing functioning over a person's life span. According to the World Health Organization, functioning can serve as foundation for a comprehensive picture of health and augment the biomedical perspective with a broader and more comprehensive picture of health as it plays out in people's lives. The crucial importance of information about patient's functioning for a well-performing health system, however, has yet to be sufficiently appreciated. Methods: This paper argues that functioning information is fundamental in all components of health systems and enhances the capacity of health systems to optimize patients' health and health-related needs. Results and conclusion: Beyond making sense of biomedical disease patterns, health systems can profit from using functioning information to improve interprofessional collaboration and achieve cross-cutting disease treatment outcomes. Implications for rehabilitation: Functioning is a key health outcome for rehabilitation within health systems. Information on restoring, maintaining, and optimizing human functioning can strengthen health system response to patients' health and rehabilitative needs. Functioning information guides health systems to achieve cross-cutting health outcomes that respond to the needs of the growing number of individuals living with chronic and multiple health conditions. Accounting for individuals functioning helps to overcome fragmentation of care and to improve interprofessional collaboration across settings